Low Physical Function in Maintenance Hemodialysis Patients Is Independent of Muscle Mass and Comorbidity - Marcus, Robin L; LaStayo, Paul C; Ikizler, T Alp; Wei, Guo; Giri, Ajay; Chen, Xiaorui; Morrell, Glen; Painter, Patricia; Beddhu, Srinivasan (Journal of renal nutrition, 2015)
It is unknown whether muscle wasting accounts for impaired physical function in adults on maintenance hemodialysis (MHD). Observational study. Outpatient dialysis units and a fall clinic. One hundred eight MHD and 122 elderly nonhemodialysis (non-HD) participants. Mid-thigh muscle area was measured by magnetic resonance imaging. Physical function was measured by distance walked in 6 minutes. Compared with non-HD elderly participants, MHD participants were younger (49.2 ± 15.8 vs. 75.3 ± 7.1 years; P < .001) and had higher mid-thigh muscle area (106.2 ± 26.8 vs. 96.1 ± 21.1 cm2; P = .002). However, the distance walked in 6 minutes was lower in MHD participants (322.9 ± 110.4 vs. 409.0 ± 128.3 m; P < .001). In multiple regression analysis adjusted for demographics, comorbid conditions, and mid-thigh muscle area, MHD patients walked significantly less distance (-117 m; 95% confidence interval: -177 to -56 m; P < .001) than the non-HD elderly. Even when compared with elderly non-HD participants, younger MHD participants have poorer physical function that was not explained by muscle mass or comorbid conditions. We speculate that the uremic milieu may impair muscle function independent of muscle mass. The mechanism of impaired muscle function in uremia needs to be established in future studies.